Business Psychology and Organisational Behaviour / A Student's Handbook - Mckenna Eugene (Psychology Press, Ltd, 2006)
Perspectives and Enquiry, Historical Influences and Research Methodology, The Individual, Personality, Intelligence and Psychological Testing, Motivation and Job Design, Perception, Communication, Learning and Memory, Information-Processing and Individual Decision Making, Attitudes and Values and Job Satisfaction and Commitment, The Group, Groups, Teambuilding, Leadership and Management Style, Power and Politics and Conflict, The Organisation, Organisational Structure and Design, Organisational Structure, Organisational Change and Development, Management and Organisational Issues, Human Resource Practices: Selection and Appraisal, Human Resource Practices: Rewards and Training and Development, Health and Work: Stress, Glossary, References, Author and Subject Index.